Efficacy of daily supplementation of 800 IU vitamin D on vitamin D status at 6 months of age in term healthy Indian infants. (November 2018) - Priyadarshi, Mayank; Sankar, Mari; Gupta, Nandita; Agarwal, Ramesh; Paul, Vinod; Deorari, Ashok
Abstract Objectives Most authorities recommend daily supplementation of 400 IU vitamin D for all term healthy neonates throughout infancy, however this dose was shown to be inadequate in an earlier study from our institution. We planned to evaluate if supplementation of 800 IU/day in term Indian infants would reduce the prevalence of vitamin D insufficiency (VDI) at 6 months of age. Methods In a prospective study, we supplemented 800 IU/day of vitamin D in 70 term infants from birth till 6 months of age. Serum 25-hydroxy cholecalciferol [25(OH)D] was measured at birth and 6 months for all infants; and at 6, 10 and 14 weeks of age in subsets of 23 infants each. The primary outcome was prevalence of VDI (defined as serum 25(OH)D level < 50 nmol/L) at 6 months of age. Results A total of 58 out of 70 (83%) infants were followed up until 6 months of age. The median (nmol/L; IQR) serum 25(OH)D at birth and 6 months of age was 25 (12.5–35) and 92.5 (72.5–137.5), respectively. The prevalence of VDI at birth was 91.3% (63/69), which reduced to 6.9% (4/58) at 6 months of age. However, four infants (6.9%, 95% CI 1.9–16.7) developed vitamin D excess (serum 25(OH)D 250–375 nmol/L) requiring reduction of the dose of supplementation. No infant developed vitamin D toxicity (serum 25(OH)D > 375 nmol/L). Conclusions Daily supplementation of 800 IU of vitamin D resulted in vitamin D sufficiency in most term healthy infants at 6 months of age but with potential risk of toxicity.